THE FACTORS EFFECT THE EXTERNEL BONDED PATCH REPAİRED IN LAMİNATED COMPOSİTE MATERİALS - PIHTILI, Haşim,Şükrü,Çetinkaya, Hayri,Yıldırım (My University, 2015)
İn this study, glass and carbon fibres reinforced composite materials have been produced with eight laminates. For experimental study, specimens with 10 mm internal hole were prepared. Then, these specimens have been repaired by using adhesive and composite patches with different parameters in necessary curing temperatures and laboratory conditions. By performing the unidirectional tensile test, the ultimate failure loads of these repaired specimens were indicated. By comparing these ultimate failure loads of repaired specimens that prepared with different parameter, the effects of several repair parameters on the ultimate failure strength are investigated. These repair parameters are patch bonded area (D/W ratio), adhesive thickness, patch thickness and fibres orientation angles (0, 15, 30, 45).
Tabakalı Kompozit Malzelerde Yapıştırıcı Kullanılarak Yama ile yapılan Tamiri Etkileyen Faktörlerin Araştırılması
Makale - Yabancı Dilde Makale
Keywords: Laminate Composite Materials bonded repair patch adhesive failure strength